Political bloggers and the personalisation of political participation - Mohamed, Shafizan (Aabid Raja Publisher, 2017)
his study argues that political blogging challenges traditional understanding of political participation that defines politics as ultimately institutional and electoral. By focusing specifically on the experiences of the Malaysian political bloggers who are generally confined within a very closed and elitist political culture, this study captures how blogging empowers everyday citizens to be involved in politics. These bloggers are able to become political by personalising issues and politics according to their own interpretations. Through intensive interviews that focused on the bloggers own understanding of their blogging experiences, the study found that these bloggers were able to see themselves as important political players by positioning themselves as the authority, the political centre and the public figure.